Anti-doping and legitimacy: an international survey of elite athletes' perceptions - Efverström, A.; Ahmadi, N.; Hoff, D.; Bäckström, Å. (International Journal of Sport Policy and Politics, 2016)
Anti-doping work is a comprehensive enterprise that entails control and governance of elite athletes` everyday lives. However, in policy-making regarding doping and anti-doping in elite sports, the athletes` perspective has not been considered adequately. Focusing on elite athletes` perceptions of anti-doping as both principle and praxis, the study aimed to analyse how these perceptions can be understood from a legitimacy perspective. A survey study involving 261 elite athletes from 51 different countries and four international sports federations was conducted. The results showed that the athletes did not question the legitimacy of the rules, but had concerns about the legitimacy of the way the rules and principles are enforced in practice, specifically with regard to matters of privacy, lack of efficiency and equal conditions as well as athletes` involvement in the anti-doping work. The article describes how athletes` perceptions of the legitimacy of anti-doping work constitute the basis for their willingness to follow regulations as well as a precondition for the work`s functionality and stability. In light of this finding, the article calls for the empowerment of athletes in anti-doping work.